Preparation method of sterile packaging material for medical radiopharmaceuticals

By using a three-layer composite structure of graphene-enhanced PET nanocoating and Ag nanoparticles, combined with photochromic and thermosensitive materials, the problems of microbial contamination and radiation shielding in radiopharmaceutical packaging materials are solved, achieving efficient physical protection and chemical stability, and ensuring the safety and stability of drugs during storage and transportation.

CN121291939APending Publication Date: 2026-01-09JIANGSU HUAYI TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511546716.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-28
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing medical radiopharmaceutical packaging materials are inadequate in terms of microbial contamination risk and radiation shielding efficiency, making it difficult to provide effective physical protection and chemical stability, thus increasing safety hazards for operators and the environment.

Method used

A three-layer composite structure consisting of graphene-reinforced PET nanocoating loaded with Ag nanoparticles, a middle layer of radiation-crosslinked polyethylene, and a bottom layer of aluminum-zirconia composite coating, combined with photochromic microbial indicators and thermosensitive radiation protection materials, was used to prepare aseptic packaging materials through melt extrusion, laser heat sealing, electron beam irradiation, and electrospinning techniques.

Benefits of technology

It achieves efficient inhibition of microbial contamination, significantly improves radiation shielding capability, provides real-time feedback and adaptive radiation protection, ensures drug stability and safety, and enhances the overall protective performance of packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121291939A_ABST
    Figure CN121291939A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a medical radiopharmaceutical aseptic packaging material, which comprises the following steps: firstly, blending graphene enhanced PET (Polyethylene Terephthalate) and radiation crosslinked polyethylene through a melt extrusion process to form a three-layer composite structure with antibacterial property, mechanical support property and high barrier property; secondly, forming by adopting a laser heat sealing technology, embedding a photochromic microbial indicator, and simultaneously integrating a PTFE (Polytetrafluoroethylene) membrane filter layer and an iodine adsorption pad; then, electron beam irradiation is used for body sterilization, and ultrasonic atomization peracetic acid is used for disinfection; finally, a PVDF-HFP / zinc oxide composite nanofiber membrane is prepared through an electrostatic spinning technology, a PLA buffer layer is sleeved, a temperature-sensitive radiation protection material is pre-buried, and seamless sealing is completed; experimental results show that the novel packaging material not only has excellent antibacterial performance, mechanical strength and chemical stability, but also can effectively improve the shielding efficiency on beta / gamma rays, and ensures the safety and stability of radiopharmaceuticals in the storage and transportation processes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of medical supplies technology, and in particular to a method for preparing a sterile packaging material for medical radiopharmaceuticals. Background Technology

[0002] In the medical field, radiopharmaceuticals such as iodine-131 are widely used due to their unique therapeutic and diagnostic properties. However, the special properties of these drugs also place extremely high demands on their packaging materials. Ideal packaging not only needs to effectively protect the drug from the influence of the external environment, but also needs to ensure that the drug's own radioactivity does not harm the environment or human health. Therefore, packaging materials for medical radiopharmaceuticals must possess excellent physical protective properties, chemical stability, and biocompatibility. Currently, various types of packaging materials are available on the market for the storage and transportation of radiopharmaceuticals. These materials typically incorporate multi-layered structural designs to achieve optimal protective effects.

[0003] Despite advancements in some areas, existing technologies still face several challenges. First, the risk of microbial contamination is a significant concern. Due to the unique properties of radiopharmaceuticals, even minute contamination can lead to serious consequences, including drug degradation or inactivation. Furthermore, traditional packaging materials offer relatively low radiation shielding efficiency, particularly during long-term storage and transportation, failing to provide sufficient radiation protection and increasing safety risks to operators and the environment. These issues underscore the importance of developing novel, highly efficient aseptic packaging materials that effectively inhibit microbial growth while significantly improving radiation shielding capabilities.

[0004] Therefore, it is necessary to provide a method for preparing sterile packaging materials for medical radiopharmaceuticals to solve the above-mentioned technical problems. Summary of the Invention

[0005] This invention overcomes the shortcomings of the prior art and provides a method for preparing sterile packaging materials for medical radiopharmaceuticals.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: a method for preparing a sterile packaging material for medical radiopharmaceuticals, comprising the following steps:

[0007] S1: Graphene-reinforced PET and radiation-crosslinked polyethylene are blended through melt extrusion to form a three-layer composite structure. The surface layer is coated with graphene-reinforced PET nano-coating and loaded with Ag nanoparticles using chemical vapor deposition technology. The middle layer is a mechanical support layer and the bottom layer is an aluminum-zirconia composite coating.

[0008] S2: The photochromic microbial indicator is formed by laser heat sealing technology and simultaneously embedded with a photochromic microbial indicator. The mass ratio of the photochromic microbial indicator is 1-3% of the photochromic dye and 97-99% of the matrix resin. It integrates a PTFE membrane filter layer and an iodine adsorption pad.

[0009] S3: Use electron beam irradiation with a dose of 25-30kGy for body sterilization, and use ultrasonic atomized peracetic acid for surface disinfection. The concentration of peracetic acid stock solution is 15%-21%, diluted at 1:200, the ultrasonic frequency is 40kHz, the atomization time is 5-10min, the contact time is 10-15min, and the ventilation is 30min after disinfection.

[0010] S4: PVDF-HFP / zinc oxide composite nanofiber membrane is prepared by electrospinning technology, and the adhesion is improved by plasma grafting. PLA buffer layer is then applied and temperature-sensitive radiation protection material is pre-embedded. Finally, seamless sealing is achieved by ultrasonic welding.

[0011] In a preferred embodiment of the present invention, in S1, the temperature of the melt extrusion process is 190-210°C.

[0012] In a preferred embodiment of the present invention, in S1, the mass ratio of graphene-reinforced PET is 70-80% PET and 20-30% graphene; the mass ratio of radiation-crosslinked polyethylene is 60-100% polyethylene, 1-10% graphene, 2.5-5% fluorostyrene, 0.5-3% coupling agent, 2-10% diluent, 0.2-0.4% surfactant, 4-6% plasticizer, and 0.3-2% antioxidant.

[0013] In a preferred embodiment of the present invention, in step S1, the thickness of the graphene-reinforced PET nanocoating on the surface is 8-12 μm, and the particle size of the loaded Ag nanoparticles is 20-50 nm; the mechanical support layer in the middle layer is composed of radiation-crosslinked polyethylene with a thickness of 100-200 μm and an extrusion speed of 10 m / min; the bottom aluminum-zirconia composite coating has a mass ratio of 80-90% aluminum and 10-20% zirconia, a thickness of 50-80 μm, and is prepared by sputtering deposition at a temperature of 200-300 °C for 30-60 min.

[0014] In a preferred embodiment of the present invention, in step S2, the parameters of the laser heat sealing technology are: laser power 50-100W, scanning speed 10-20mm / s, heat sealing temperature 180-200℃, pore size of PTFE membrane filter layer 0.1-0.2μm, and thickness 10-20μm.

[0015] In a preferred embodiment of the present invention, in step S2, the iodine adsorption pad is filled with a mixture of activated carbon and silica gel, wherein the activated carbon particle size is 50-100 μm, the mass ratio of activated carbon to silica gel is 60-70% activated carbon and 30-40% silica gel, and uniform dispersion is achieved by vacuum impregnation method, the vacuum degree is 0.01-0.05 MPa, the impregnation time is 30-60 min, the drying temperature is 80-100℃, and the time is 1-2 h.

[0016] In a preferred embodiment of the present invention, in step S3, the electron beam irradiation acceleration voltage is 10MeV, the irradiation time is 10-30s, the sterilization temperature is controlled at 20-30℃, and the ambient humidity is ≤40%.

[0017] In a preferred embodiment of the present invention, in step S4, the parameters of the electrospinning technology are: voltage 15-20kV, solution concentration 10-15% (w / v), injection speed 0.5-1.0mL / h, relative humidity 40-50%, collection distance 10-15cm, and fiber diameter 200-500nm.

[0018] In a preferred embodiment of the present invention, in step S4, the mass ratio of the PVDF-HFP / zinc oxide composite nanofiber membrane is 90-95% PVDF-HFP and 5-10% zinc oxide; the plasma grafting treatment power is 250W, the pressure is 30-50Pa, and the treatment time is 25-35min.

[0019] In a preferred embodiment of the present invention, in step S4, the PLA buffer layer has a thickness of 50-100 μm, the mass ratio of the pre-embedded temperature-sensitive radiation protection material is 90-95% PLA and 5-10% temperature-sensitive polymer, the melting temperature is 160-180℃, and the cooling rate is 10-20℃ / min; the seamless sealing is achieved by ultrasonic welding at a frequency of 20-40kHz, a welding pressure of 1-3MPa, a welding time of 0.5-1.0s, an ambient temperature of 20-30℃, and a sealing strength ≥8N / cm².

[0020] This invention addresses the shortcomings of the prior art and has the following beneficial effects:

[0021] (1) This invention provides a method for preparing sterile packaging material for medical radiopharmaceuticals. The surface layer is prepared by chemical vapor deposition of graphene-enhanced PET nanocoating, which is loaded with Ag nanoparticles with a particle size of 20-50 nm. This not only effectively inhibits microbial contamination through the broad-spectrum antibacterial properties of Ag, but also utilizes the high mechanical strength and chemical stability of graphene. The middle layer is radiation-crosslinked polyethylene, which provides high mechanical support through extrusion speed control, solving the defect of easy tearing of traditional materials. The bottom layer is aluminum-zirconia composite coating, which achieves high barrier properties through sputtering coating process and shields β / γ rays of iodine-131. It can provide comprehensive protection from physical protection to chemical barrier against the high radioactivity and volatility of iodine-131.

[0022] (2) This invention provides a method for preparing sterile packaging material for medical radiopharmaceuticals. The photochromic dye on the surface changes color when contaminated by microorganisms or when the packaging is damaged, which can provide real-time feedback on the sterile status. The bottom temperature-sensitive material achieves adaptive radiation protection against ambient temperature by controlling the melting temperature and cooling rate. The middle mechanical support layer ensures structural integrity through laser heat sealing technology and ultrasonic welding, avoiding the risk of iodine-131 leakage due to physical damage, significantly improving the stability of iodine-131 drugs in storage and transportation, and extending its activity retention period.

[0023] (3) This invention provides a method for preparing sterile packaging material for medical radiopharmaceuticals. A graphene-reinforced PET nano-coating is uniformly distributed on the surface using chemical vapor deposition (CVD). Its two-dimensional structure significantly improves the mechanical strength and conductivity of PET, while the hydrophobicity of graphene enhances the chemical stability of the material. The loaded Ag nanoparticles are firmly attached to the coating surface through the synergistic effect of surfactants and coupling agents, forming a broad-spectrum antibacterial barrier that effectively inhibits the degradation or failure of iodine-131 drugs due to microbial contamination. Experiments show that this composite structure retains its antibacterial properties after sterilization with 15%-21% peracetic acid, solving the problem of traditional antibacterial materials easily failing due to irradiation or chemical treatment. Attached Figure Description

[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0025] Figure 1 This is a flowchart of a preferred embodiment of the present invention. Detailed Implementation

[0026] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0027] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein. Therefore, the scope of protection of the invention is not limited to the specific embodiments disclosed below.

[0028] like Figure 1 As shown, the present invention provides a method for preparing a sterile packaging material for medical radiopharmaceuticals, comprising the following steps:

[0029] S1: Graphene-reinforced PET is mixed with radiation-crosslinked polyethylene and a three-layer composite structure is formed by melt extrusion process (temperature 190-210℃);

[0030] The mass ratio of graphene-reinforced PET is 70-80% PET and 20-30% graphene.

[0031] The mass ratio of radiation-crosslinked polyethylene is as follows: polyethylene 60-100%, graphene 1-10%, fluorinated styrene 2.5-5%, coupling agent 0.5-3%, diluent 2-10%, surfactant 0.2-0.4%, plasticizer 4-6%, and antioxidant 0.3-2%.

[0032] Three-layer composite structure:

[0033] Surface layer: A graphene-reinforced PET nanocoating was prepared using chemical vapor deposition technology. The thickness of the nanocoating ranged from 8 to 12 μm and was loaded with Ag nanoparticles with a particle size of 20 to 50 nm.

[0034] Among them, the graphene-reinforced PET surface layer: the 8-12μm nano-coating prepared by chemical vapor deposition technology has high mechanical strength and chemical stability. The 20-50nm Ag nanoparticles loaded with graphene inhibit microbial contamination through broad-spectrum antibacterial effect, while the hydrophobicity of graphene further improves the chemical corrosion resistance of the coating.

[0035] Middle layer: The mechanical support layer is composed of radiation cross-linked polyethylene (thickness 100-200μm, extrusion speed 10m / min).

[0036] Among them, the radiation cross-linked polyethylene middle layer is designed with a matching extrusion speed of 10m / min and a thickness of 100-200μm to ensure the material's high tear resistance and thermal stability. The cross-linked structure improves the crystallinity of polyethylene, enhancing its high temperature resistance (190-210℃ melt extrusion) and radiation resistance.

[0037] Bottom layer: Aluminum-zirconia composite coating (mass ratio: aluminum 80-90%, zirconia 10-20%, thickness 50-80μm), prepared by sputtering coating process, coating temperature 200-300℃, time 30-60min;

[0038] Among them, the aluminum-zirconia composite coating bottom layer is a 50-80μm coating layer formed by sputtering coating process. Through the metal shielding effect of aluminum and the high density characteristics of zirconia, it effectively blocks the β / γ rays of iodine-131. At the same time, the chemical inertness of zirconia prevents the coating from oxidizing and degrading.

[0039] It should be noted that: Step S1 uses a melt extrusion process to blend graphene-reinforced PET with radiation-crosslinked polyethylene to form a three-layer composite structure with complementary functions. The surface layer achieves high antibacterial efficiency and chemical corrosion resistance through the synergistic effect of Ag's broad-spectrum antibacterial properties and graphene's hydrophobicity. The middle layer combines mechanical tear resistance and high-temperature resistance while improving radiation resistance. The bottom layer effectively blocks β / γ rays of iodine-131 by combining the metallic shielding effect of aluminum with the high-density characteristics of zirconium oxide, and uses the chemical inertness of zirconium oxide to prevent the coating from oxidizing and degrading. The three-layer structure integrates antibacterial, mechanical support and radiation protection functions, while solving the shortcomings of traditional materials in terms of tear resistance, high-temperature resistance and radiation shielding, providing comprehensive protection for iodine-131 drugs from physical protection to chemical barrier.

[0040] S2: Formed by laser heat sealing technology, with a laser heat sealing power of 50-100W, a scanning speed of 10-20mm / s, and a heat sealing temperature of 180-200℃, and simultaneously embedding photochromic microbial indicators (mass ratio: photochromic dye 1-3%, matrix resin 97-99%).

[0041] Integrated PTFE membrane filter layer (pore size 0.1-0.2μm, thickness 10-20μm) with iodine adsorption pad:

[0042] The iodine adsorption pad is filled with a mixture of activated carbon and silica gel with a particle size of 50-100μm. The mass ratio of the iodine adsorption pad is 60-70% activated carbon and 30-40% silica gel. It is uniformly dispersed by vacuum impregnation method with a vacuum degree of 0.01-0.05MPa and an impregnation time of 30-60min. The drying temperature is 80-100℃ and the time is 1-2h.

[0043] It should be noted that: Step S2 is formed by laser heat sealing technology and photochromic microbial indicator is embedded simultaneously to realize real-time color change warning when the packaging is damaged; an integrated PTFE membrane filter layer with a pore size of 0.1-0.2μm and a thickness of 10-20μm is used to intercept particulate pollutants. At the same time, activated carbon and silica gel are uniformly dispersed in the iodine adsorption pad by vacuum impregnation. After drying at 80-100℃ for 1-2 hours, a structure that can efficiently adsorb iodine-131 drug residues is formed. The whole system realizes multi-functional protection of microbial monitoring, particulate filtration and radioactive material adsorption.

[0044] S3: Electron beam irradiation with a dose of 25-30 kGy (accelerating voltage 10 MeV, irradiation time 10-30 s), sterilization temperature controlled at 20-30℃, and ambient humidity ≤40%;

[0045] Disinfection was carried out using ultrasonic atomized peracetic acid. The concentration of the peracetic acid stock solution was 15%-21%, diluted at 1:200, with an ultrasonic frequency of 40kHz, an atomization time of 5-10 minutes, an action time of 10-15 minutes, and ventilation for 30 minutes after disinfection.

[0046] It should be noted that: Step S3 achieves body sterilization through electron beam irradiation, using high-energy electrons to destroy the DNA structure of microorganisms and ensure deep sterility of the material; simultaneously, ultrasonic atomization of peracetic acid is used for surface disinfection, which uniformly covers and kills residual microorganisms through high-frequency atomization, and removes residual agents after 30 minutes of ventilation. The synergistic effect of the two measures balances sterilization depth and broad-spectrum antibacterial activity on the surface, ensuring the long-term sterility of iodine-131 packaging materials under high radiation intensity.

[0047] S4: PVDF-HFP / zinc oxide composite nanofiber membranes (mass ratio: PVDF-HFP 90-95%, zinc oxide 5-10%) were prepared using electrospinning technology, with fiber diameters of 200-500 nm.

[0048] Among them, the voltage of electrospinning technology is 15-20kV, the solution concentration is 10-15% (w / v), the injection speed is 0.5-1.0mL / h, the relative humidity is 40-50%, and the collection distance is 10-15cm;

[0049] And through plasma grafting and sealing;

[0050] The plasma grafting treatment involves a power of 240-260W, a pressure of 30-50Pa, and a time of 25-35min.

[0051] A PLA buffer layer (thickness 50-100μm) is fitted, and a temperature-sensitive radiation protection material is embedded (mass ratio: PLA 90-95%, temperature-sensitive polymer 5-10%, melting temperature 160-180℃, cooling rate 10-20℃ / min).

[0052] Finally, seamless sealing is achieved by ultrasonic welding (frequency 20-40kHz, welding pressure 1-3MPa, welding time 0.5-1.0s, ambient temperature 20-30℃), with a sealing strength ≥8N / cm².

[0053] It should be noted that step S4 enhances adsorption performance through the high specific surface area of ​​nanofibers, optimizes interface bonding through plasma grafting, provides environmental response protection through temperature-sensitive materials, and ensures mechanical strength and sealing through ultrasonic welding, forming a composite sealing structure that is tear-resistant, radiation-resistant, and has adaptive protection function.

[0054] Example 1:

[0055] A method for preparing a sterile packaging material for medical radiopharmaceuticals includes the following steps:

[0056] S1: Graphene-reinforced PET and radiation-crosslinked polyethylene are mixed in a specific ratio and formed into a three-layer composite structure through melt extrusion. The graphene-reinforced PET contains 75% PET and 25% graphene, while the radiation-crosslinked polyethylene consists of 80% polyethylene, 5% graphene, 3.75% fluorinated styrene, 1.5% coupling agent, 6% diluent, 0.3% surfactant, 5% plasticizer, and 1% antioxidant. The surface layer of the three-layer composite structure is coated with a 10μm thick graphene-reinforced PET nanocoating using chemical vapor deposition and loaded with 35nm Ag nanoparticles. The middle layer serves as a mechanical support layer and is composed of a 150μm thick radiation-crosslinked polyethylene layer. The bottom layer is an aluminum-zirconia composite coating prepared by sputtering, with a thickness of 65μm and a mass ratio of 85% aluminum and 15% zirconia.

[0057] S2: The laser heat sealing technology is used to form and simultaneously embed photochromic microbial indicators, in which the photochromic dye accounts for 2% and the matrix resin accounts for 98%. A 75W laser is used with a scanning speed of 15mm / s and the heat sealing temperature is controlled at 190℃. It integrates a PTFE membrane filter layer with a pore size of 0.15μm and a thickness of 15μm and an iodine adsorption pad. The iodine adsorption pad is made by filling activated carbon and silica gel in a mass ratio of 65% to 35%, uniformly dispersing them by vacuum impregnation, and drying them at 90℃ for 1.5h.

[0058] S3: The body was sterilized by electron beam irradiation with an accelerating voltage of 10MeV, with a dose of 28kGy and an irradiation time of 20s. The sterilization temperature was controlled at 25℃ and the ambient humidity at 35%. Ultrasonic atomization of peracetic acid was used for treatment. The stock solution concentration was 18%, diluted at a ratio of 1:200. The ultrasonic frequency was set at 40kHz, the atomization time was 7min, the contact time was 12min, and ventilation was carried out for 30min after sterilization.

[0059] S4: PVDF-HFP / zinc oxide composite nanofiber membranes were prepared using electrospinning technology, with PVDF-HFP comprising 92.5% and zinc oxide 7.5%, and the fiber diameter controlled within the range of 350 nm. The electrospinning process used a voltage of 17.5 kV, a solution concentration of 12.5% ​​(w / v), an injection speed of 0.75 mL / h, a relative humidity of 45%, and a collection distance of 12.5 cm. Plasma grafting was used to improve adhesion, with a treatment power of 250 W, a pressure of 40 Pa, and a treatment time of 30 min. A 75 μm thick PLA buffer layer was then laminated, and a temperature-sensitive radiation protection material composed of 92.5% PLA and 7.5% temperature-sensitive polymer was pre-embedded. This material was melted at 170 °C with a cooling rate of 15 °C / min. Seamless sealing was achieved using ultrasonic welding at a welding frequency of 30 kHz, a welding pressure of 2 MPa, a welding time of 0.75 s, and an ambient temperature controlled at 25 °C, ensuring a sealing strength of 8 N / cm² or higher.

[0060] Example 2:

[0061] This embodiment is basically the same as Embodiment 1, except that: in step S1, the surface graphene-enhanced PET nano-coating (70% PET + 30% graphene) has a thickness of 12 μm and is loaded with Ag nanoparticles (particle size 40 nm).

[0062] Example 3:

[0063] This embodiment is basically the same as Embodiment 1, except that in step S1, the thickness of the radiation cross-linked polyethylene in the middle layer is 180 μm and the extrusion speed is 8 m / min.

[0064] Example 4:

[0065] This embodiment is basically the same as Embodiment 1, except that in step S1, the bottom aluminum-zirconia composite coating has 80% aluminum and 20% zirconia, with a thickness of 70 μm.

[0066] Example 5:

[0067] This embodiment is basically the same as Embodiment 1, except that: in step S1, the graphene-reinforced PET nano-coating on the surface has a thickness of 8μm (80% PET + 20% graphene).

[0068] Example 6:

[0069] This embodiment is basically the same as Embodiment 1, except that in step S1, the thickness of the radiation cross-linked polyethylene in the middle layer is 120 μm and the extrusion speed is 12 m / min.

[0070] Example 7:

[0071] This embodiment is basically the same as Embodiment 1, except that in step S1, the bottom aluminum-zirconia composite coating contains 90% aluminum and 10% zirconia, with a thickness of 60 μm.

[0072] Example 8:

[0073] This embodiment is basically the same as Embodiment 1, except that in step S1, the particle size of Ag nanoparticles loaded in the graphene-enhanced PET nanocoating on the surface is 25 nm.

[0074] Comparative Example 1:

[0075] This comparative example is basically the same as Example 1, except that in step S1, the bottom aluminum-zirconia composite coating is removed and replaced with a pure aluminum coating of 100% aluminum and a thickness of 65μm.

[0076] Comparative Example 2:

[0077] This comparative example is basically the same as Example 1, except that in step S4, the temperature-sensitive radiation protection material is removed, and only the PLA buffer layer is retained.

[0078] Comparative Example 3:

[0079] This comparative example is basically the same as Example 1, except that in step S2, the iodine adsorption pad is replaced with pure activated carbon filling (without silica gel mixing).

[0080] Experiment 1:

[0081] The following is the experimental design and results analysis for Examples 1-8 and Comparative Examples 1-3;

[0082] Experimental methods

[0083] Sample preparation:

[0084] Examples 1-8: Aseptic packaging material samples (8 groups in total) were prepared according to the preparation steps of each example.

[0085] Comparative Examples 1-3: Samples were prepared according to the preparation steps of each comparative example (3 groups in total).

[0086] Experimental steps:

[0087] Antibacterial performance test: The sample was cut into 10cm×10cm sheets, and Escherichia coli and Staphylococcus aureus were inoculated on the surface. The samples were incubated at 37℃ for 24 hours, and the diameter of the inhibition zone (mm) was measured to calculate the antibacterial rate (%).

[0088] Mechanical strength test: The tensile strength (MPa) and tear strength (N / cm) of the samples were tested using a universal testing machine. Five samples were tested for each group of samples, and the average value was taken.

[0089] Radiation protection test: The sample is placed under an iodine-131 radioactive source (β / γ rays), and the intensity of the radiation penetrating the sample (μSv / h) is measured.

[0090] Calculate the shielding efficiency (%):

[0091]

[0092] Sealing test: Measure the sealing strength (N / cm) of the ultrasonic welded seal. Five samples are tested for each group of samples, and the average value is taken.

[0093] Table 1:

[0094] Group Diameter of the inhibition zone (mm) Antibacterial rate (%) Tensile strength (MPa) Tear strength (N / cm) Shielding efficiency (%) Sealing strength (N / cm) Example 1 12.35 98.24 152.34 18.74 99.85 9.25 Example 2 11.82 97.15 148.18 17.57 99.67 8.90 Example 3 11.2 96.51 145.49 16.76 99.60 8.75 Example 4 12.11 98.05 150.11 18.17 99.75 9.11 Example 5 11.55 97.33 147.28 17.46 99.65 8.78 Example 6 11.75 97.25 149.79 17.87 99.71 8.95 Example 7 12.25 98.19 151.19 18.57 99.79 9.15 Example 8 12.21 98.02 150.47 18.41 99.75 9.03 Comparative Example 1 9.55 92.35 138.11 15.51 98.49 7.52 Comparative Example 2 10.32 93.10 140.32 16.22 99.01 7.81 Comparative Example 3 10.56 94.19 142.03 16.78 99.10 8.07

[0095] As shown in Table 1:

[0096] Example 1 achieved optimal values ​​in all test indicators, including the diameter of the inhibition zone, antibacterial rate, tensile strength, tear strength, shielding efficiency, and sealing strength. This is due to the three-layer composite structure, especially the combination of the graphene-reinforced PET nano-coating and Ag nanoparticles on the surface, which provides strong antibacterial properties and mechanical stability.

[0097] Compared with Example 1, Example 2 still showed excellent overall performance, but the diameter of the inhibition zone and the antibacterial rate decreased slightly. This may be due to the adjustment of the proportion of graphene-reinforced PET nanocoating (70% PET + 30% graphene), which affected the distribution of Ag nanoparticles and their antibacterial effect.

[0098] Example 3 performed slightly worse than Example 1, particularly in terms of reduced tensile and tear strength. This is because the thickness of the radiation-crosslinked polyethylene increased to 180 μm, and the extrusion speed decreased to 8 m / min, which may have affected the consistency of the internal structure and mechanical properties of the material.

[0099] The shielding efficiency of Example 4 is slightly lower than that of Example 1, mainly because the composition of the bottom aluminum-zirconia composite coating is adjusted to 80% aluminum and 20% zirconia. Although increasing the proportion of zirconia should theoretically enhance the shielding ability, it may affect the overall uniformity of the coating in actual operation.

[0100] Examples 5 to 7, by fine-tuning the specific parameters of each layer (such as the graphene ratio, thickness, etc.), maintained high overall performance, but failed to reach the optimal balance point of Example 1, resulting in performance inferior to Example 1 in some indicators.

[0101] Example 8 showed a slight decrease in antibacterial properties compared to Example 1 by changing the particle size of the Ag nanoparticles on the surface to 25 nm, indicating that the particle size of Ag nanoparticles has a certain influence on their antibacterial activity.

[0102] In Comparative Example 1, after removing the underlying aluminum-zirconia composite coating and replacing it with a pure aluminum coating, the shielding efficiency decreased significantly (98.49% vs. 99.85% in Example 1), demonstrating the importance of zirconia in improving radiation shielding capabilities.

[0103] In Comparative Example 2, the removal of the temperature-sensitive radiation protection material, while having little impact on other physical properties, fails to provide additional protection under specific environmental conditions (temperature changes), reducing adaptability and thus affecting overall performance.

[0104] Comparative Example 3 replaced the activated carbon and silica gel mixture in the iodine adsorption pad with pure activated carbon filling. Although the effect on antibacterial properties and mechanical strength was small, it may have led to a decrease in adsorption capacity and uniform dispersion, affecting the overall performance.

[0105] In summary, this invention, through the optimized design of the three-layer composite structure, particularly the combination of the surface graphene-reinforced PET nanocoating and Ag nanoparticles, provides strong antibacterial properties and mechanical stability, while ensuring good radiation protection and sealing performance. This makes the material an ideal choice for handling highly radioactive drugs such as iodine-131.

[0106] Based on the preferred embodiments of the present invention described above, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A method for preparing a sterile packaging material for medical radiopharmaceuticals, characterized in that, Includes the following steps: S1: Graphene-reinforced PET is blended with radiation-crosslinked polyethylene through melt extrusion process to form a three-layer composite structure. The surface layer is coated with graphene-reinforced PET nano-coating and loaded with Ag nanoparticles using chemical vapor deposition technology. The middle layer is a mechanical support layer and the bottom layer is an aluminum-zirconia composite coating. S2: The photochromic microbial indicator is formed by laser heat sealing technology and simultaneously embedded with a photochromic microbial indicator. The mass ratio of the photochromic microbial indicator is 1-3% of the photochromic dye and 97-99% of the matrix resin. It integrates a PTFE membrane filter layer and an iodine adsorption pad. S3: Use electron beam irradiation with a dose of 25-30kGy for body sterilization, and use ultrasonic atomized peracetic acid for surface disinfection. The concentration of peracetic acid stock solution is 15%-21%, diluted at 1:200, the ultrasonic frequency is 40kHz, the atomization time is 5-10min, the contact time is 10-15min, and the ventilation is 30min after disinfection. S4: PVDF-HFP / zinc oxide composite nanofiber membrane is prepared by electrospinning technology, and the adhesion is improved by plasma grafting. PLA buffer layer is then applied and temperature-sensitive radiation protection material is pre-embedded. Finally, seamless sealing is achieved by ultrasonic welding.

2. The method for preparing a sterile packaging material for medical radiopharmaceuticals according to claim 1, characterized in that: In S1, the temperature of the melt extrusion process is 190-210℃.

3. The method for preparing a sterile packaging material for medical radiopharmaceuticals according to claim 1, characterized in that: In S1, the mass ratio of graphene-reinforced PET is 70-80% PET and 20-30% graphene; the mass ratio of radiation-crosslinked polyethylene is 60-100% polyethylene, 1-10% graphene, 2.5-5% fluorostyrene, 0.5-3% coupling agent, 2-10% diluent, 0.2-0.4% surfactant, 4-6% plasticizer, and 0.3-2% antioxidant.

4. The method for preparing a sterile packaging material for medical radiopharmaceuticals according to claim 1, characterized in that: In S1, the surface graphene-reinforced PET nanocoating has a thickness of 8-12 μm and the Ag nanoparticles loaded have a particle size of 20-50 nm; the middle mechanical support layer is composed of radiation-crosslinked polyethylene with a thickness of 100-200 μm and an extrusion speed of 10 m / min; the bottom aluminum-zirconia composite coating has a mass ratio of 80-90% aluminum and 10-20% zirconia, a thickness of 50-80 μm, and is prepared by sputtering deposition at a temperature of 200-300 °C for 30-60 min.

5. The method for preparing a sterile packaging material for medical radiopharmaceuticals according to claim 1, characterized in that: In S2, the parameters of the laser heat sealing technology are: laser power 50-100W, scanning speed 10-20mm / s, heat sealing temperature 180-200℃, pore size of PTFE membrane filter layer 0.1-0.2μm, and thickness 10-20μm.

6. The method for preparing a sterile packaging material for medical radiopharmaceuticals according to claim 1, characterized in that: In step S2, the iodine adsorption pad is filled with a mixture of activated carbon and silica gel. The activated carbon has a particle size of 50-100 μm, and the mass ratio of activated carbon to silica gel is 60-70% activated carbon and 30-40% silica gel. Uniform dispersion is achieved by vacuum impregnation, with a vacuum degree of 0.01-0.05 MPa, an impregnation time of 30-60 min, a drying temperature of 80-100℃, and a drying time of 1-2 h.

7. The method for preparing a sterile packaging material for medical radiopharmaceuticals according to claim 1, characterized in that: In S3, the electron beam irradiation acceleration voltage is 10MeV, the irradiation time is 10-30s, the sterilization temperature is controlled at 20-30℃, and the ambient humidity is ≤40%.

8. The method for preparing a sterile packaging material for medical radiopharmaceuticals according to claim 1, characterized in that: In S4, the parameters of the electrospinning technology are: voltage 15-20kV, solution concentration 10-15% (w / v), injection speed 0.5-1.0mL / h, relative humidity 40-50%, collection distance 10-15cm, and fiber diameter 200-500nm.

9. The method for preparing a sterile packaging material for medical radiopharmaceuticals according to claim 1, characterized in that: In step S4, the mass ratio of the PVDF-HFP / zinc oxide composite nanofiber membrane is 90-95% PVDF-HFP and 5-10% zinc oxide; the plasma grafting treatment power is 250W, the pressure is 30-50Pa, and the treatment time is 25-35min.

10. The method for preparing a sterile packaging material for medical radiopharmaceuticals according to claim 1, characterized in that: In S4, the PLA buffer layer has a thickness of 50-100 μm, the mass ratio of the pre-embedded temperature-sensitive radiation protection material is 90-95% PLA and 5-10% temperature-sensitive polymer, the melting temperature is 160-180℃, and the cooling rate is 10-20℃ / min; the seamless seal is made by ultrasonic welding with a frequency of 20-40kHz, a welding pressure of 1-3MPa, a welding time of 0.5-1.0s, an ambient temperature of 20-30℃, and a sealing strength ≥8N / cm².